Glucagon-like peptide-1 stimulates acute secretion of pro-atrial natriuretic peptide from the isolated, perfused pig lung exposed to warm ischemia - Balk-Møller, Emilie; Hebsgaard, Mathilde M. B.; Lilleør, Nikolaj B.; Møller, Christian H.; Gøtze, Jens P.; Kissow, Hannelouise (Frontiers in Transplantation, 2022)
Glucagon-like peptide-1 (GLP-1) has proven to be protective in animal models of lung disease but the underlying mechanisms are unclear. Atrial natriuretic peptide (ANP) is mainly produced in the heart. As ANP possesses potent vaso- and bronchodilatory effects in pulmonary disease, we hypothesised that the protective functions of GLP-1 could involve potentiation of local ANP secretion from the lung. We examined whether the GLP-1 receptor agonist liraglutideGLP-1 was able to improve oxygenation in lungs exposed to two hours of warm ischemia and if GLP-1liraglutide stimulated ANP secretion from the lungs in the porcine ex vivo lung perfusion (EVLP) model. Pigs were given a bolus of 40 µg/kg liraglutide or saline one hour prior to sacrifice. The lungs were then left in vivo for two hours, removed en bloc and placed in the EVLP machinery. Lungs from the liraglutide treated group were further exposed to liraglutide in the perfusion buffer (1.125 mg). Main endpoints were oxygenation capacity, and plasma and perfusate concentrations of proANP and inflammatory markers. Lung oxygenation capacity, plasma concentrations of proANP or concentrations of inflammatory markers were not different between groups. ProANP secretion from the isolated perfused lungs were markedly higher in the liraglutide treated group (area under curve for the first 30 minutes in the liraglutide group: 635 ± 237 pmol/l x min vs. 38 ± 38 pmol/l x min in the saline group) (p < 0.05). From these results, we concluded that GLP-1liraglutide potentiated local ANP secretion from the lungs.